2019
DOI: 10.21873/anticanres.13974
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dose Distributions When Using Carbon Ion Radiotherapy Versus Intensity-modulated Radiotherapy for Hepatocellular Carcinoma With Macroscopic Vascular Invasion: A Retrospective Analysis

Abstract: Background/Aim: This study compared the dose distributions of carbon ion radiotherapy (C-ion RT) and intensity-modulated radiotherapy (IMRT) in patients with locally advanced hepatocellular carcinoma (LAHCC). Patients and Methods: A retrospective analysis was conducted in 10 consecutive patients with LAHCC who had undergone C-ion RT. The dose-volume histogram parameters of clinical plans using C-ion RT at 60 Gy and simulated plans using IMRT at 60 Gy and 50 Gy were compared. We measured the percentage of the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Primarily, TMIH and non-invasiveness are the crucial considerations for decision-making ( 7 12 ). What is more, CIRT possesses multidimensional superiorities compared with either photon or proton radiotherapy ( 21 , 29 , 63 , 64 ). CIRT is superior to SABR for treating patients with liver cancer due to its unique advantages in terms of target conformity and normal liver tissue sparing, relative biological effectiveness (RBE), duration of treatment, risk of subsequent primary cancers, and so on ( 20 , 21 , 29 , 30 , 35 , 63 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, TMIH and non-invasiveness are the crucial considerations for decision-making ( 7 12 ). What is more, CIRT possesses multidimensional superiorities compared with either photon or proton radiotherapy ( 21 , 29 , 63 , 64 ). CIRT is superior to SABR for treating patients with liver cancer due to its unique advantages in terms of target conformity and normal liver tissue sparing, relative biological effectiveness (RBE), duration of treatment, risk of subsequent primary cancers, and so on ( 20 , 21 , 29 , 30 , 35 , 63 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…What is more, CIRT possesses multidimensional superiorities compared with either photon or proton radiotherapy ( 21 , 29 , 63 , 64 ). CIRT is superior to SABR for treating patients with liver cancer due to its unique advantages in terms of target conformity and normal liver tissue sparing, relative biological effectiveness (RBE), duration of treatment, risk of subsequent primary cancers, and so on ( 20 , 21 , 29 , 30 , 35 , 63 68 ). Additionally, CIRT is beneficial to protect the immune system and activate specific anti-cancer immunity by triggering the immunoreaction on account of its excellent superiorities in the aspects of dose localization and RBE ( 21 28 ), which is extremely significant for patients to fight against cancer and SARS-CoV-2 synchronously ( 7 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…C-ion RT delivers higher local doses than X-ray RT (i.e., stereotactic body RT and intensity-modulated RT) [ 8 , 9 ]; also, the modality enables delivery of a reduced dose to the liver while ensuring good target coverage. Therefore, the effect on liver function is minimal, and exacerbation of poor liver function and radiation-induced liver disease after C-ion RT are rare [ 3 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of carbon-ion radiotherapy (C-ion RT) to treat HCC has shown favorable clinical results, with minimal liver damage [ 3 6 ]. These favorable results are due to the biological and physical advantages that C-ion RT has over X-ray RT [ 7 9 ]. However, C-ion RT for HCC with HE presents technical difficulties in patients who cannot maintain a static position during irradiation due to flapping tremor or disturbance of consciousness.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, particle RT can obtain a satisfactory dose distribution with very few beams (only two to four beams are usually required). Recently, a number of studies (4)(5)(6)(7)(8)(9)(10)(11)(12) have reported promising clinical outcomes with particle therapy for various tumors.…”
Section: Introductionmentioning
confidence: 99%